Enhancing students’ speaking skills using ChatGPT application in ESP maritime English learning - Ratnaningsih, Dyah (JEES (Journal of English Educators Society), 2025)
This research investigated the impact of utilizing ChatGPT, an advanced artificial intelligence language model, on improving maritime English-speaking skills among students at a maritime polytechnic in Indonesia. Effective communication in maritime operations is critical for maintaining safety, preventing misunderstandings, and ensuring efficient coordination among multinational crew members. However, many maritime students face challenges in attaining adequate English-speaking proficiency necessary for these operations. This study adopted a classroom action research (CAR) design involving 69 students over two instructional cycles. Data collection methods included pretests and post-tests to quantitatively measured speaking performance, alongside questionnaires to gather qualitative insights into students’ perceptions of the learning process and their engagement. Quantitative data were analyzed using paired sample t-tests in SPSS 22, revealing statistically significant improvements in key areas such as vocabulary use, grammatical accuracy, and overall fluency after the introduction of ChatGPT-assisted learning activities. Additionally, qualitative findings from questionnaires indicated enhanced student confidence, motivation, and active participation in speaking tasks, suggesting positive attitudes toward this AI-supported learning approach. The study highlighted the potential of integrating ChatGPT as a supplementary instructional tool within maritime English curricula to support language acquisition more effectively. By fostering maritime English-speaking competence through innovative technology integration, this approach contributed to better preparation of students for real-world communication demands in the maritime industry. Ultimately, the findings demonstrated that ChatGPT can serve as a valuable resource for language instructors, promoting more engaging, interactive, and productive learning environments that align with the operational needs of global maritime professionals.